2011
DOI: 10.1097/jcn.0b013e318215bb78
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Self-concept and Adherence to Therapeutic Regimens in Patients With Heart Failure

Abstract: A direct relationship between challenge to self-concept and adherence to prescribed regimen was noted (P < .01); threat to self-concept had an inverse relationship to adherence (P < .01). In other words, patients who faced more challenge and less threat to self-concept adhered more to the prescribed therapeutic regimen. Through education and counseling, nurses can empower their patients to perceive HF as a challenge to better adhere to the prescribed therapeutic regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 22 publications
1
30
0
1
Order By: Relevance
“…The inclusion of several other psychosocial factors (self-efficacy, social support, and hostility) may have accounted for the null finding in the latter study. Health satisfaction (20) and self-concept (79,80) were associated with higher self-care in other studies, but only univariable associations were reported. Locus of control was no significant determinant of medication adherence in a study in which the impact of medication burden and beliefs were included as well (62).…”
Section: Other Cognitive Determinantsmentioning
confidence: 86%
See 1 more Smart Citation
“…The inclusion of several other psychosocial factors (self-efficacy, social support, and hostility) may have accounted for the null finding in the latter study. Health satisfaction (20) and self-concept (79,80) were associated with higher self-care in other studies, but only univariable associations were reported. Locus of control was no significant determinant of medication adherence in a study in which the impact of medication burden and beliefs were included as well (62).…”
Section: Other Cognitive Determinantsmentioning
confidence: 86%
“…A number of cross-sectional studies examined other cognitive determinants of self-care, such as perceived control (16,42), locus of control (62), self-concept (79,80), and health satisfaction (20) (Table S1, Supplemental Digital Content 1, http://links.lww.com/PSYMED/A255). One study of high quality reported a significant association between perceived control and self-care beyond disease severity, comorbidities, and HF knowledge (42), whereas it was not associated with being novice, expert, and inconsistent in self-care in another study (16).…”
Section: Other Cognitive Determinantsmentioning
confidence: 99%
“…In other studies, general non-adherence in HF patients was reported at 16%, 26 and mean adherence of 50.3 on a 0−100 scale in another. 27 General adherence instruments can be useful in screening patients for perceived issues with adherence, but may not clearly identify all adherence issues. The high levels of adherence reported by participants in this study raises question about whether the participants were over reporting or if perhaps this group is an example of higher adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of existing interventions to promote self-management adherence in rural heart failure patients include: lack of theoretical guidance for the development of a rural-based intervention 18, 19 , unclear mechanism of intervention 8, 17, 20 , and reliance on self-report measures of self-management adherence 2123 .…”
Section: Study Rationalementioning
confidence: 99%